Textually-Mediated Synonymy in English / Arabic Translation - Issa, Hiba (2011)
A Master of Arts Thesis in Translation and Interpreting (English/Arabic/English) by Hiba Issa entitled, "Textually-Mediated Synonymy in English / Arabic Translation." Thesis advisor is Dr. Basil Hatim and was submitted in December 2011. Available are both hard and soft copies of the thesis.